Investigation of sandstone erosion by continuous and pulsed water jets. (June 2019) - Raj, Piush; Hloch, Sergej; Tripathi, Rupam; Srivastava, Madhulika; Nag, Akash; Klichová, Dagmar; Klich, Jiří; Hromasová, Monika; Muller, Miroslav; Miloslav, Linda; Chattopadhyaya, Somnath; Adamcik, Pavel
Abstract: The study compares the sandstone erosion manifestations (depth, width, and volume of the removed material) caused by continuous and pulsed water jets (WJs) with a frequency f = 20 kHz and 40 kHz. The WJ head follows an inclined trajectory at an angle of 45° to the horizontal surface. The starting point of the head was positioned 5 mm above the sandstone surface. The traverse speed of the head was varied from v = 0.25 mm/s to 1 mm/s. The structural changes and plastic deformation caused by the mechanical effect of the continuous and pulsed WJs were analysed using SEM and optical profilometer. The results showed that an optimal standoff distance was responsible for the maximum erosion effect under both continuous and pulsed regimes. The PWJ at f = 40 kHz showed better erosion performance in terms of depth (6.8 mm), width (6.83 mm) and volume removed (27.31 mm 3 ) as compared to PWJ at f  = 20 kHz and CWJ. The microstructural topography at varying standoff distance ( z  = 10 mm to 45 mm) showed erosion features such as micro-pits, cracks, perforated holes responsible for different erosion stages. On-line monitoring via means of acoustic emission was measured to evaluate the erosion phenomenon on the sandstone surface during the impact of the PWJ and CWJ. The correlation between the acoustic emission results and the erosion parameters showed the progression of the erosion process under different technological conditions.